Inflation Expectations Anchoring Across Different Types of Agents : the Case of South Africa - Miyajima, Ken (IMF Working Papers; Working Paper ;, 2018)
Inflation forecasts are modelled as monotonically diverging from an estimated long-run anchor point, or 'implicit anchor', towards actual inflation as the forecast horizon shortens. Fitting the model with forecasts by analysts, businesses and trade unions for South Africa, we find that inflation expectations have become increasingly strongly anchored. That is, the degree to which the estimated implicit anchor pins down inflation expectations at longer horizons has generally increased. Estimated inflation anchors of analysts lie within the 3-6 percent inflation target range of the central bank. However, the implicit anchors of businesses and trade unions, who are directly involved in the setting of wages and prices that drive the inflation process, have remained above the top end of the official target range. Possible explanations for these phenomena are discussed.